The Rules of The Dhabt of The Quran and The Law of Writing in The Mushaf of The Qur'an - Ahmad Fihri; Dinil Abrar Sulthoni; Imron Baehaqi; Anwar Nuris (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
The study of the science of Qur'ānic dhabt in this paper aims to provide a specific explanation of the rules of dhabt and the law of writing in the Qur'ānic mushaf. This effort is necessary considering that there are various models of writing and their use so that the validity of the meaning of the Qur'an can be maintained. The method used in this study is a qualitative method with a literature study approach. Literature analysis in this study is based on two primary sources, namely Samir at-Thalibin fi ar-Rasmi wa Dhabth al-Kitab al-Mubin by Ali Muhammad ad-Dhabba' and Irsyad at-Thalibin Ila Dhabth al-Kitab al-Mubin by Muhammad Sâlim Muhaisîn. Based on the analysis that has been done, it is known that the rules of dhabt science explain specifically about the marking of vowels and tannins, writing tannin signs related to the end of the word, writing rules for tannin signs related to the letter after it, writing rules for Nun Sakinah signs related to the letter after it, writing rules for Ikhtilas Izharum and Imalah signs, writing rules for Tasydid signs, writing rules for Tasydid signs, writing rules for Mad signs, writing rules for Izhar and Idgham signs, writing rules for hamzah signs. Opinions, there are those who disallow them (Abdullah ibn Umar ra, Abdullah ibn Mas'ud ra, Qatadah, Ibn Sirin, who allow (al-Kisa'i, Rabi'ah bi Abdurrrahman, al-Laits, Abu al- Aswad, etc.).